Two-Way Street: Ambassadors Sharing the Road - Gonzalez, Adriana; Kearns, Sara K.; Martin, Darchelle; Reed, Jason B. (American Library Association, 2017)
Ambassadors are more than student volunteers that choose to dedicate their time toward the libraries; we are active and engaged members of the student body that believe that the libraries are worthy of time and investment. The ambassadors not only acknowledge the library as a crucial part of our campus, but we devote our time and talents toward increasing its value for all students and faculty. (Ambassador Interview)
Keywords: Student Ambassadors; Academic Libraries